Innovative ecosystems behind regional smart specializations: The role of social, cognitive and geographical proximity - Elżbieta Wojnicka-Sycz; Marcin Kaczyński; Piotr Sycz (Journal of Entrepreneurship, Management and Innovation)
The article shows how regional smart specializations that are currently considered as the most essential tool of European innovation policy may be assessed if they form innovative ecosystems based on social, cognitive, and geographical proximity. The article presents the concepts of smart specializations and innovative ecosystems, as well as the concept of proximity and its aspects being of reference to smart specialization ideas. The concept of innovative ecosystems is presented from the perspective of its foundations and relations to other concepts and theories. Cooperation in the innovation process by varied actors is considered a significant feature of innovative ecosystems and the manifestation of social proximity. Related diversity of smart specialization areas indicates their cognitive proximity, and embeddedness in a particular administrative region shows their geographical proximity. The results of research carried out in the Subcarpathian region prove that firms in smart specializations are more Research & Development and innovation-intensive and more prone to cooperation than other companies, which determines their social proximity. The research also shows that smart specializations have positive effects on regional development, which indicates the efficiency of their innovative ecosystems. Related diversity of Subcarpathian Regional Smart Specializations (RSS) is also measured to show their cognitive proximity. Analysis of the locations of RSS companies indicates that they are characterized not only by regional but often even by local geographical proximity. The applied methods are desk research, web site queries, a literature review, statistical data analysis, as well as direct research based on a survey and econometric analysis of the results of the survey. The article responds to the lack of studies on smart specializations in the context of proximity.